A Low-quiescent Current Full on-chip 1.2 V CMOS Low Drop-Out Regulator - Pérez Bailón, Jorge; Calvo, Belén; Medrano, Nicolás (Jornada de Jóvenes Investigadores del I3A, 2017)
This paper presents a fully-integrated low-power 0.18 µm CMOS Low-Dropout (LDO) regulator for battery operated portable devices. It provides an accurate 1.2 V output voltage from 3.3 V to 1.3 V input voltages up with only 5.9 µA quiescent current, including an all-MOS 0.4 V reference voltage.